Power up: patient and public involvement in developing a shared decision-making app for mental health - Edridge, Chloe; Edbrooke-Childs, Julian; Martin, Kate; Delane, Louise; Averill, Phoebe; Feltham, Amy; Rees, Jessica; Jeremy, Grace; Chapman, Louise; Craven, Michael P.; Wolpert, Miranda (Archetype Health, 2018)
Background The importance of patient and public involvement (PPI) in designing interventions to support young people’s mental health is becoming a central tenet of the research process. Existing research has indicated that co-design with service users may help to engender multiple improvements in research projects, from design through to applications of study findings. Aims The aim of this study is to examine our experience of making the involvement of young people an ongoing part of the research process. We report on PPI in relation to a feasibility trial of the development of an app called Power Up, which is designed to support shared decision-making in mental health. Method Young people, carers, and clinicians were involved in each aspect of the project from governance, needs and environment analysis, to development and revisions of the Power Up smartphone app intended for use within child and adolescent mental health services. Involvement was achieved through ongoing contributions to steering groups, co-design workshops, and interviews. The project model was approached as a cyclical multidirectional process of ideas, PPI input, reflection, and alterations. Conclusion PPI was embedded into the project model from the outset, to be iterative and cyclical informing the development and direction of the digital tool at each stage. Involving service users resulted in the identification and implementation of multiple changes to the app, both conceptual and tangible. Several challenges associated with PPI were also encountered, warranting future research and discussion.